Anal dysplasia in adolescent and young adult men who have sex with men: a single-center retrospective and descriptive study (2010–2020) - Addison, Jessica; Assefa, Ida; Woods, Elizabeth R.; Fitzgerald, Susan (Frontiers in Pediatrics, 2023)
Objective: There are limited studies evaluating anal cytology results or the prevalence of anal human papiloma virus (HPV) in adolescent and young adult (AYA) men who have sex with men (MSM). The purpose of this study was to review anal cytology screening results and determine whether abnormal findings resulted in completion of anoscopy in AYA MSM (13-26 years old). Patients and Methods: This was a retrospective study evaluating 84 anal Papanicolaou screening results among 36 AYA MSM patients 13-26 years who had an anal Papanicolaou test completed at an outpatient Adolescent/Young Adult Medicine Practice at Boston Children’s Hospital; an urban, non-profit, academic, free-standing children’s hospital from January 1, 2010, to December 31, 2020. Results: The findings of anal Papanicolaou screening included atypical squamous cells of undetermined significance (ASCUS) (37%), negative for squamous intraepithelial lesion (31%), inability to read (21.3%), and low-grade squamous intraepithelial lesion (10.8%). Most patients who had ASCUS results were referred for anoscopy (n=28, 90.3%), and of those referred only 6.5% (n=2) completed an anoscopy (Table 2). Of those with low-grade squamous cell intraepithelial lesion (LGSIL) results, 88.9% (n=8) were referred for anoscopy, and among those who were referred, only 3.3% (n=3) had completed an anoscopy. Conclusion: This study showed that there were abnormalities in cytology when anal Papanicolaou test screening was performed in this population, and the completion rates for anoscopy were low.